Anthracnose (Colletotrichum spp.) in forestry nurseries. - Arguedas-Gamboa, Marcela (2012)
The paper describes the characteristics of the “anthracnose” disease (Colletotrichum spp.), as well as plant hosts, disease symptoms, life cycle and disease management practices in forestry nurseries. In Costa Rica, this disease has been reported in species such as Acacia mangium, Araucaria sp., Astronium graveolens, Dypterix panamensis, Ceiba pentandra, Dalbergia retusa, Eryobotria japonica, Erythrina poeppigiana, Eucalyptuscinerea, Eucalyptus deglupta, Gliricidia sepium, Hymenaea courbaril, Inga edulis, Samanea saman, Terminalia catappa, Trichilia havanensis y Vochysia guatemalensis.